The functional roles of TCA cycle metabolites in cancer - Eniafe, Joseph; Jiang, Shuai (Oncogene, 2021)
The tricarboxylic acid cycle (TCA cycle) has been known for decades as a hub for generating cellular energy and precursors for biosynthetic pathways. Several cancers harbor mutations that affect the integrity of this cycle, mostly at the levels of isocitrate dehydrogenase (IDH), succinate dehydrogenase (SDH), and fumarate hydratase (FH). This results in dysregulation in the production of TCA cycle metabolites and is probably implicated in cancer initiation. By modulating cellular activities, including metabolism and signaling, TCA cycle intermediates are able to impact the processes of cancer development and progression. In this review, we discuss the functional roles of the TCA cycle intermediates in suppressing or promoting the progression of cancers. A further understanding of TCA metabolites’ roles and molecular mechanisms in oncogenesis would prompt developing novel metabolite-based cancer therapy in the future.